Profile of adult patients with stroke treated in a clinical school of physical therapy - Barbosa, Rafael Alves; Vasconcelos, Thiago Brasileiro; de Sousa, Cristiano Teles; Costa, Micheline Freire Alencar; dos Santos, Mayara Paz Albino; Bastos, Vasco Pinheiro Diógenes (Journal of Health Care, 2017)
This study aimed to delineate the specific epidemiological profile of patients with sequelae of stroke treated in a clinical school of physical therapy. This is a documentary study with a cross-sectional quantitative analysis of the results. The average age of the patients was 53.77 (Â±9.52) years, with prevalence of ischemic stroke (69.23%; n=9); the profession of merchant, associated with males with ischemic stroke, had the higher incidence (23.08%; n=3). The most significant risk factor was the hypertension (61.54%; n=8); and the most significant sequelae were hemiplegic gait (46.15%; n=6) and unequal motor movement on the left (23.08%; n=3) and right (23.08%, n=3) side of the body; and kinesiotherapy was the predominant type of treatment (69.23%, n=9). Male patients with a mean age of 53.77 years, merchants, diagnosed with ischemic stroke were the epidemiological profile of this research. Between the related sequelae, the unequal motor movement on the left and right side of the body and the hemiplegic gait were enhanced.